Function moves biomolecular condensates in phase space. (3rd March 2022) - Feric, Marina; Misteli, Tom
Abstract: Phase separation underlies the formation of biomolecular condensates. We hypothesize the cellular processes that occur within condensates shape their structural features. We use the example of transcription to discuss structure–function relationships in condensates. Various types of transcriptional condensates have been reported across the evolutionary spectrum in the cell nucleus as well as in mitochondrial and bacterial nucleoids. In vitro and in vivo observations suggest that transcriptional activity of condensates influences their supramolecular structure, which in turn affects their function. Condensate organization thus becomes driven by differences in miscibility among the DNA and proteins of the transcription machinery and the RNA transcripts they generate. These considerations are in line with the notion that cellular processes shape the structural properties of condensates, leading to a dynamic, mutual interplay between structure and function in the cell. Abstract : Transcriptional condensates challenge the popular biological paradigm that "structure determines function." We suggest the process of de novo RNA production during transcription shapes the structural organization of biomolecular condensates as they sample different points in phase space whilst actively transcribing.